The measures and treatments of the Prophet of God Yusuf ((peace be upon him)) Egypt’s economic crisis -a historical study- through Surat Yusuf in the Noble Qur’an - Al Raifai, Abdul Basit; Al-Abassi, Ala’a (Al-Adab Journal, 2023)
The economic crisis that occurred in Egypt during the periods of time in which the Pharaohs ruled, and which was contemplated by the Prophet of God Joseph - peace be upon him - is a very difficult crisis for the Egyptians at that time, especially on the issue of hunger and drought, as the warning of this crisis came through a vision that had The pharaoh saw her sleeping, and the details of the events of this crisis and the measures to address them in the Noble Qur’an were mentioned exclusively in Surat Yusuf. The ability of Prophet Yusuf - peace be upon him - to manage this crisis was cleared and cleared to rid the Egyptians of its danger, which was inevitable to afflict and harm them, which is hunger and death, as he undertook several measures, including: Working to increase the area of agricultural lands with a lot of irrigation and land reclamation projects, as it has spread among the Egyptians a culture of rationalization of consumption starting from the ruling class and ending with the simplest classes of society, and also built warehouses and equipped them to ensure the safety of storing agricultural crops, as he made things in his hands so that he could To apply procedures and measures on the ground to ensure that the crisis can be confronted and escaped safely, knowing that this crisis has struck the countries near and surrounding Egypt. Through news about this crisis through the Noble Qur’an, some vocabulary and words that have an economic connotation, such as price, merchandise, measure, dirhams and other vocabulary, were mentioned, as the economic characteristic was inherent to the subject of the crisis in its events and ways of dealing with it.